2020
DOI: 10.1371/journal.pone.0235699
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the uptake of cataract surgery and interventions to improve uptake in low- and middle-income countries: A systematic review

Abstract: Despite significant evidence around barriers hindering timely access to cataract surgery in low-and middle-income countries (LMICs), little is known about the strategies necessary to overcome them and the factors associated with improved access. Despite significant evidence that certain groups, women for example, experience disproportionate difficulties in access, little is known about how to improve the situation for them. Two reviews were conducted recently: Ramke et al., 2018 reported experimental and quasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 49 publications
(143 reference statements)
0
18
0
Order By: Relevance
“…We anticipate that the level of evidence across the challenges is variable, so a range of evidence synthesis approaches will be required. For example, several systematic or scoping reviews have been done to assess cataract services in terms of access, coverage, quality, and equity, 12 , 13 , 14 but not productivity. The number and quality of studies within these reviews vary greatly; a review that focused on equity was limited to low-income and middle-income countries and identified only two studies from rural China, 13 whereas a review that focused on global quality identified 143 studies, predominantly (65%) from high-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…We anticipate that the level of evidence across the challenges is variable, so a range of evidence synthesis approaches will be required. For example, several systematic or scoping reviews have been done to assess cataract services in terms of access, coverage, quality, and equity, 12 , 13 , 14 but not productivity. The number and quality of studies within these reviews vary greatly; a review that focused on equity was limited to low-income and middle-income countries and identified only two studies from rural China, 13 whereas a review that focused on global quality identified 143 studies, predominantly (65%) from high-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the cost of surgery, the difficulty of travelling to a faraway hospital may be a deterrent to some patients who require a family member to accompany them, whether for accessibility reasons in the case of people with certain types of impairments, but also for social reasons in the case of particularly older women [25]. Outreach camps, particularly where transport to the surgical services is provided, may overcome accessibility issues associated with both disability and gender that have been identified in other rural settings [19,26]. Physical accessibility to hospital facilities could still be an issue, despite the infrastructure improvements that were made after conducting accessibility audits, and may account for differences in service uptake.…”
Section: Discussionmentioning
confidence: 99%
“…[ 54 , 55 ]. For example, for those that live in low-resource areas, there can be cultural, social, and economic factors impacting cataract outcomes, including countries such as Nepal, China, Madagascar, Kenya, Ghana, the Philippines and Bangladesh [ 34 , 56 , 57 ]. Ocular symptoms of cataracts include double vision, seeing halos in the line of vision, light sensitivity, clouded/blurred vision, the need for additional light when reading and additional activities, and frequent changes in prescription for contact lenses or glasses [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological risk factors for cataracts include age [ 61 ], sex [ 34 , 62 , 63 ], living in a low-resourced area [ 56 , 57 , 61 , 64 ], educational status [ 65 ], smoking [ 66 , 67 ], diabetes [ 50 , 68 ], and environmental factors [ 69 ]. Cataracts may appear in the eye when a patient is in their 40s or 50s, although may not start to impact their vision until they are in their 60s [ 58 ].…”
Section: Introductionmentioning
confidence: 99%